2009
DOI: 10.1080/00050060802630353
|View full text |Cite
|
Sign up to set email alerts
|

Still living in a war zone: Perceived health and wellbeing of partners of Vietnam veterans attending partners' support groups in New South Wales, Australia

Abstract: Post-traumatic stress disorder (PTSD) in veterans is well documented, less so the long-term impact on the health of their partners and families. The perceived health and wellbeing of women partners of Australian Vietnam veterans who were members of partners of veterans support groups is reported. This qualitative study used data from 76 participants in 10 focus groups in metropolitan, regional, and rural and remote areas of New South Wales (NSW). The data were tape-recorded, transcribed and thematically analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 36 publications
7
38
0
Order By: Relevance
“…Many wrote about their deteri orating relationships and resulting feelings of sadness, isolation, anger, and stress. Our findings corroborate previous accounts of PTSD's detrimental effects on relationship quality (Meis et al, 2010), partner distress (Lambert et al, 2012), and behavioral adaptation among caregivers and families (Outram et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Many wrote about their deteri orating relationships and resulting feelings of sadness, isolation, anger, and stress. Our findings corroborate previous accounts of PTSD's detrimental effects on relationship quality (Meis et al, 2010), partner distress (Lambert et al, 2012), and behavioral adaptation among caregivers and families (Outram et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Those who had known their partner before he began to show symptoms of traumatization were particularly likely to construct the veteran as being sick, as they had been aware of a time when he was by all accounts healthy and functioning well. In these cases, the concept of ambiguous loss (Boss, ) can help explain the women's sense of their partner being physically present but emotionally absent, an observation also reported in other qualitative studies of the experiences of veterans’ partners (Dekel, Goldblatt et al., ; Frederikson et al., ; Nir et al., ; Outram et al., ).…”
Section: Discussion/conclusionmentioning
confidence: 69%
“…That the women felt it necessary to walk on eggshells has been reported elsewhere in the qualitative literature exploring the lived experiences of veterans' female partners in other countries (Outram, Hansen, MacDonell, Cockburn, & Adams, 2009;Verbosky & Ryan, 1988), which was similarly understood as a way to prevent escalation of anger and conflict within relationships. Additionally, participants in this study also reported wanting to protect their veteran partners from having to deal with the difficulties of everyday life and repressing their own emotional responses as a way to cope with their partner's unpredictability, which are also findings which have been reported elsewhere by female partners of veterans (Frederikson, Chamberlain, & Long, 1996;Lyons, 2001).…”
Section: Discussion/conclusionmentioning
confidence: 81%
See 1 more Smart Citation
“…Participants in our study were consistent in their comments about the support they found with other partners, over and above more general carer support, highlighting the very specific nature of being in a relationship with a male veteran with PTSD. This need for specific peer support is a consistent theme in the literature (Outram et al, 2009;Sherman et al, 2005). "Lack of understanding," together with a related subtheme of "invisibility" was particularly pronounced in participants' descriptions of their experiences with health providers and with the DVA.…”
Section: Discussionmentioning
confidence: 85%